2020
DOI: 10.1155/2020/8730918
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Galectin-3 and Early Herpes Zoster Neuralgia and Postherpetic Neuralgia: A Retrospective Clinical Observation

Abstract: This study aims to explore the value of serum galectin-3 in patients with herpes zoster neuralgia (HZN) and postherpetic neuralgia (PHN) and other factors influencing HZN and PHN occurrence. Samples from forty patients with herpes zoster neuralgia (HZN) (Group H), 40 patients with nonherpes zoster neuralgia (Group N), and 20 cases of health check-up were collected. Patients were divided into PHN group (Group A) and non-PHN group (Group B) according to the occurrence of PHN in Group H. Galectin-3, T-lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…The genetic polymorphisms of the galectin-3-encoding gene affected the course of enterovirus 71 infection in children, which was partially associated with diverse viral replication according to the gene variant [33]. Increased serum galectin-3 has been observed in patients with varicella-zoster virus infection and patients with herpes zoster neuralgia and post-herpetic neuralgia presented with higher concentrations [17]. In human immunodeficiency virus infection, galectin-3 has been shown to support the attachment of the virus to macrophages and CD4+ T cells [19,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic polymorphisms of the galectin-3-encoding gene affected the course of enterovirus 71 infection in children, which was partially associated with diverse viral replication according to the gene variant [33]. Increased serum galectin-3 has been observed in patients with varicella-zoster virus infection and patients with herpes zoster neuralgia and post-herpetic neuralgia presented with higher concentrations [17]. In human immunodeficiency virus infection, galectin-3 has been shown to support the attachment of the virus to macrophages and CD4+ T cells [19,34].…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 is released by inflammatory cells, mainly macrophages, endothelial cells, and epithelial cells. It is found in spleen, stomach, colon, liver, kidney, heart, uterus, ovary, pancreas, and lungs (alveolar cells) [15,17]. Galectin-3 has been previously studied in relation to several viral infections in human, including human immunodeficiency virus, herpesvirus-1 infection, influenza, early herpes zoster neuralgia, and postherpetic neuralgia [15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research results also revealed that in PHN patients, Gal-3 and IL-6 plasma levels were considerably higher than in normal people [12]. It can be used as an early diagnosis and a predictor of PHN [24]. In this study, it was found that Gal-3 and IL-6 levels in the patients' plasma in the group of internal heat acupuncture combined with high-voltage long-duration PRF decreased significantly at 4 and 12 weeks after treatment, implying that the effect of internal heat acupuncture on eliminating skin nerve endings inflammation was more lasting.…”
Section: Discussionmentioning
confidence: 76%
“…1k ). Importantly, in the context of pain pathogenesis, Gal3 was reported to play a critical role in neuropathic pain in a peripheral nerve injury model 20,21 . Hence, we were interested in validating, at a protein level, Gal3 is a marker for HIPAs.…”
Section: Resultsmentioning
confidence: 99%